Genetic and chemical disruption of amyloid precursor protein processing impairs zebrafish sleep maintenance - Güliz Gürel Özcan; Sumi Lim; Thomas Canning; Lavitasha Tirathdas; Joshua Donnelly; Tanushree Kundu; Jason Rihel (iScience, 2024)
Summary: Amyloid precursor protein (APP) is a brain-rich, single pass transmembrane protein that is proteolytically processed into multiple products, including amyloid-beta (Aβ), a major driver of Alzheimer disease (AD). Although both overexpression of APP and exogenously delivered Aβ lead to changes in sleep, whether APP processing plays an endogenous role in regulating sleep is unknown. Here, we demonstrate that APP processing into Aβ40 and Aβ42 is conserved in zebrafish and then describe sleep/wake phenotypes in loss-of-function appa and appb mutants. Larvae with mutations in appa had reduced waking activity, whereas larvae that lacked appb had shortened sleep bout durations at night. Treatment with the γ-secretase inhibitor DAPT also shortened night sleep bouts, whereas the BACE-1 inhibitor lanabecestat lengthened sleep bouts. Intraventricular injection of P3 also shortened night sleep bouts, suggesting that the proper balance of Appb proteolytic processing is required for normal sleep maintenance in zebrafish.